Validation of the Brazilian version of WHODAS 2.0 in patients on hemodialysis therapy - Shamyr Sulyvan Castro; Camila Ferreira Leite; Juliana Elisa Baldin; Marilita Falangola Accioly (Editora Champagnat, 2018)
Abstract Introduction: Chronic kidney disease and hemodialysis normally have an impact on the functioning. Objective: To validate the Brazilian version of the World Health Organization Disability Assessment Schedule 2.0 in individuals with chronic kidney disease on hemodialysis treatment. Methods: The 36-item version was applied to interview 51 individuals with chronic kidney disease undergoing dialysis treatment. To ascertain the instrument's applicability, its internal consistency and test-retest stability were studied. To check the validity, a convergent/divergent analysis was performed. Results: The participants answered the questions on the main instrument at two timepoints and on the World Health Organization Quality of Life Abbreviated instrument and the Kidney Disease Quality of Life - Short FormTM 1.3 once each. Cronbach's α coefficient was appropriate in all domains except the "Getting along" domain. The test-retest coefficients were above the recommended value (> 0.70). Convergent and divergent validity analysis also showed consistent results by correlation coefficient assessment. Conclusion: The instrument is valid and reliable. This study supports the use of the questionnaire by presenting its appropriate psychometric properties. We suggest that some care should be taken specifically in the sexual questions of the "Getting along" domain.